Alkaline oxidization can increase the in vitro antiparasitic activity of proanthocyanidin-rich plant extracts against Ascaris suum - Imran Iqbal Bin; Engström Marica T; Karonen Maarit; Williams Andrew R; Salminen Juha-Pekka (Elsevier, 2025)
Proanthocyanidins (PAs) are a class of plant specialized metabolites with well-documented bioactivities such as antiparasitic effects. However, little is known about how the modification of PAs influences their bioactivity. The objective of this study was to investigate a wide range of PA-containing plant samples to determine if extracts containing PAs modified by oxidation had altered antiparasitic activities, compared to the original extracts that had not been modified in alkaline conditions. We extracted and analyzed samples from 61 proanthocyanidin-rich plants. The extracts were then oxidized under alkaline conditions. We used these non-oxidized and oxidized proanthocyanidin-rich extracts to conduct a detailed analysis of direct antiparasitic effects against the intestinal parasite Ascaris suum in vitro. These tests showed that the proanthocyanidin-rich extracts had antiparasitic activity. Modification of these extracts significantly increased the antiparasitic activity for the majority the extracts, suggesting that the oxidation procedure enhanced the bioactivity of the samples. Some samples that showed no antiparasitic activity before oxidation showed very high activity after the oxidation. High levels of other polyphenols in the extracts, such as flavonoids, was found to be associated with increased antiparasitic activity following oxidation. Thus, our in vitro screening opens up the opportunity for future research to better understand the mechanism of action how alkaline treatment of PA-rich plant extracts increases their biological activity and potential as novel anthelmintics.